Review: Africa and Its Historical and Contemporary Diasporas - Szeremley, Csaba (Journal of Central and Eastern European African Studies, 2025)
The volume Africa and Its Historical and Contemporary Diasporas, edited by Tunde Adeleke and Arno Sonderegger, is a fundamental collection that thoroughly examines various aspects of Africa’s historical and contemporary diasporas, particularly emphasizing their global significance. The authors adopt different approaches to exploring the diaspora’s history and present-day challenges, covering economic, political, cultural, and religious factors related to the African continent and its diaspora. The work plays a pioneering role in shifting the concept of diaspora beyond the history of slavery and colonization, placing it within broader, modern contexts. It is particularly important for readers interested in diaspora studies, postcolonial theories, and African history, as it provides a comprehensive understanding of African identities, cultures, and communities’ roles in today’s globalized world.